# Math Homework Help

### Showing All Questions Answered Popular Recommended Unanswered Editor's Choice in Math

• Math
Hello! The area of a rectangle with sides a and b is a*b. Here we have six rectangles, all of them have a=2 and the second sides are 1, 4, 9, 16, 25 and 36. Therefore the sum of the areas is equal...

Asked by user3831483 on via web

• Math
If three points lie on the same line, which means collinear, the area of the triangle formed by them is 0. Let us substitute these points in the formula of the area of a triangle, i.e. 1/2 (x1(y2...

Asked by gcrhorsepuppylover on via web

• Math
Hello! Denote the cost of supplies for a dog as d and for a cat as c (in dollars). Then the first condition may be written in terms of d and c as d=2*c. The second condition is 24*d+155*c=1152....

• Math
You need to write the characteristic equation, such that: r^2 - (1/2)r + 1/16+x-e^x = 0 You need to evaluate Delta , such that: Delta = (-1/2)^2 - 4(1/16+x-e^x) = 1/4 - 1/4 - 4x + 4e^x Delta...

Asked by user7230927 on via web

• Math
Because it is cheaper to have books shipped to San Francisco from Novato you would have all 600 shipped from there as it is only \$5 per text. Also it is cheaper to have books shipped to Sacramento...

Asked by user4769955 on via web

• Math
tan 17^0 = x/y y = x/0.3057  ---gt1 tan 21.8^0 = (x+8)/y y = (x+8)/0.3999  -----gt2 equation 1 = equation 2 = y x/0.3057 = (x+8)/0.3999 by cross-multiplication we get...

• Math
Hello! Your question is very short and I might misunderstand it. I think you mean a Cartesian product of the set of all real numbers RR and the set consisting of one element, the number 2. It is,...

Asked by user5096146 on via web

• Math
Solve 4x+3y=-5; 3x-2y=-9 by elimination: Elimination (or multiplication/addition or linear combinations) is a method that adds/subtracts multiples of one equation to multiples of the other...

Asked by abdulvakil25 on via web

• Math
We have to be careful here because of absolute value sign. We need to know where the function under absolute value changes sign (in the interval of integration), which is at x=pi in this case....

Asked by enotes on via web

• Math
Hello! Find the indefinite integral: int((sqrt(y)-y)/y^2)dy=int(y^(-3/2)-1/y)dy=(-2)*y^(-(1)/(2))-ln(y). Then substitute y from 1 to 4: (-2*4^(-1/2)-ln(4))-(-2)=-1-ln(4)+2=1-ln(4) approx -0.386.

Asked by enotes on via web

• Math
Hello! First find the indefinite integral, int(x/(2)-2/x)dx=int(x/2)dx-int(2/x)dx=(x^2)/4-2ln(x). Then substitute x from 1 to 2: (2^2/4-2ln(2))-(1^2/4-2ln(1))=1-2ln(2)-1/4=3/4-2ln(2) approx...

Asked by enotes on via web

• Math
You need to evaluate the integral, hence, you need to use the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_0^1(5x - 5^x)dx = int_0^1(5x)dx - int_0^1 5^x dx...

Asked by enotes on via web

• Math
You need to evaluate the integral, hence, you need to use the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_0^1(x^10 + 10^x)dx = int_0^1(x^10)dx + int_0^1 10^x...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(u) du = F(b) - F(a) int_(pi/4)^(pi/3) csc^2 theta d theta = int_(pi/4)^(pi/3) 1/(sin^2...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_0^(pi/4)(1+cos^2 theta)/(cos^2 theta) d theta =...

Asked by enotes on via web

• Math
Before evaluating this integral, simplify the expression in the integral using trigonometric identities. The following Pythagorean identity will be useful: tan^2(theta) + 1 = sec^2(theta) Start...

Asked by enotes on via web

• Math
We will make substitution x=t^6. Therefore, the differential is dx=6t^5dt and the new bounds of integration are t_1=root(6)(1)=1 and t_2=root(6)(64)=2. int_1^64(1+root(3)(x))/sqrt x...

Asked by enotes on via web

• Math
Hello! Consider the denominator first: sinh(x)+cosh(x)=(e^x-e^(-x))/(2) +(e^x+e^(-x))/(2)=e^x. Therefore the integrand is equal to 2 and the integral is 2*(10-(-10))=40.

Asked by enotes on via web

• Math
Hello! This integral is a table one, int(dr)/(sqrt(1-r^2))=arcsin(r)+C.   Therefore the definite integral is equal to arcsin(sqrt(3)/2)-arcsin(0)=pi/3-0=pi/3 approx 1.047. =arcsin(r)+C.

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) You need to expand the cube such that: (x-1)^3 = x^3 - 1 - 3x(x-1)...

Asked by enotes on via web

• Math
Hello! (t^2-1)/(t^4-1)=1/(t^2+1). Therefore indefinite integral is arctan(t)(+C). Substitute t from 0 to 1/sqrt(3) and obtain arctan(1/sqrt(3))-arctan(0)=pi/6-0=pi/6 approx 0.524.

Asked by enotes on via web

• Math
We have to be careful because of the absolute value. We need to know where the function under absolute values is positive and when it is negative in the given interval. It is also a good idea to...

Asked by enotes on via web

• Math
Hello! Consider two intervals: (-1, 0) and (0, 2) to simplify |x|: int_(-1)^2(x-2|x|)dx=int_(-1)^0(x-2|x|)dx+int_0^2(x-2|x|)dx= =int_(-1)^0(x+2x)dx+int_0^2(x-2x)dx=...

Asked by enotes on via web

• Math
You need to find the indefinite integral, hence, you need to remember that sec t = 1/(cos t) , such that: int (sec t)(sec t + tan t) dt = int (1/(cos t))(1 + sin t)/(cos t) dt int (sec t)(sec...

Asked by enotes on via web

• Math
You need to find the indefinite integral, hence, you need to remember that 1 + tan^2 x = 1/(cos^2 x) = (tan x)'. int (1 + tan^2 x )dx = int (tan x)' dx = tan x + c Hence, evaluating the...

Asked by enotes on via web

• Math
You need to find the indefinite integral, hence, you need to remember that sin 2x = 2sin x*cos x , such that: int (sin 2x)(sin x) dx = int (2sin x*cos x)/(sin x) dx  int (sin 2x)(sin x) dx =...

Asked by enotes on via web

• Math
You need to evaluate the integral, hence, you need to use the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_(-2)^3(x^3 - 3)dx = int_(-2)^3(x^3)dx - int_(-2)^3 3...

Asked by enotes on via web

• Math
You need to evaluate the integral, hence, you need to use the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_1^2(4x^3 - 3x^2 + 2x)dx = int_1^2(4x^3)dx - int_1^2...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_(-2)^0 ((1/2)t^4 + (1/4)t^3 - t)dt = int_(-2)^0 ((1/2)t^4 dt +...

Asked by enotes on via web

• Math
We will use linearity of integral: int(a cdot f(x)+b cdot g(x))dx=a int f(x)dx+b int g(x)dx. int_0^3(1+6w^2-10w^4)dw=int_0^3dw+6int_0^3w^2dw-10int_0^3w^4dw=...

Asked by enotes on via web

• Math
We have to evaluate the integral: \int_{0}^{2}(2x-3)(4x^2+1)dx=\int_{0}^{2}(8x^3-12x^2+2x-3)dx =[8(x^4/4)-12(x^3/3)+2(x^2/2)-3x]_{0}^{2}...

Asked by enotes on via web

• Math
You need to use the following substitution to evaluate the definite integral, such that: 1 - t = u => -dt = du int_(-1)^1 t*(1-t)^2dt = int_(u_1)^(u_2) (1 - u)*u^2 (-du) int_(u_1)^(u_2) (u...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_0^pi (5e^x+ 3sin x)dx = int_0^pi 5e^x dx + int_0^pi 3sin x...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_1^2 (1/x^2 - 4/x^3)dx = int_1^2 1/x^2 dx - int_1^2 4/x^3 dx...

Asked by enotes on via web

• Math
int_1^4(4+6u)/sqrt(u)du =int_1^4(4/sqrt(u)+(6u)/sqrt(u))du =int_1^4(4u^(-1/2)+6u^(1/2))du =[4(u^(-1/2+1)/(-1/2+1))+6(u^(1/2+1)/(1/2+1))]_1^4 =[4(u^(1/2)/(1/2))+6(u^(3/2)/(3/2))]_1^4...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_0^4(3sqrt t - 2e^t)dt = int_0^4 3sqrt tdt - int_0^4 2e^t...

Asked by enotes on via web

• Math
You need to evaluate the definite integral, such that: int_0^1 x(root(3) x + root(4) x)dx = int_0^1 (x^(1+1/3) + x^(1+1/4))dx int_0^1 x(root(3) x + root(4) x)dx = ((x^(2+1/3))/(2+1/3) +...

Asked by enotes on via web

• Math
You need to evaluate the indefinite integral, such that: int f(x)dx = F(x) + c int (x^2 - x^(-2))dx = int (x^2)dx - int x^(-2) dx  Evaluating each definite integral, using the formula int x^n...

Asked by enotes on via web

• Math
int sqrt(x^3)root(3)(x^2) dx Before evaluating, convert the radicals to expressions with rational exponents. = int x^(3/2)*x^(2/3) dx Then, simplify the integrand. Apply the laws of exponent...

Asked by enotes on via web

• Math
int (x^4-1/2x^3+1/4x-2)dx To evaluate this integral, apply the formulas int x^n dx=x^(n+1)/(n+1) +C and int adx = ax + C . int (x^4-1/2x^3+1/4x-2)dx =x^5/5 - 1/2*x^4/4 + 1/4*x^2/2-2x...

Asked by enotes on via web

• Math
int (y^3+1.8y^2-2.4y)dy To evaluate this integral, apply the formula int x^n dx = x^(n+1)/(n+1) + C . = y^4/4 + 1.8y^3/3 - 2.4y^2/2 + C =0.25y^4 + 0.6y^3 - 1.2y^2 + C Therefore, ...

Asked by enotes on via web

• Math
You need to evaluate the indefinite integral, hence, you need to open the brackets, such that: (u+4)(2u+1) = 2u^2 + 9u + 4 int (u+4)(2u+1) du = int (2u^2 + 9u + 4) du  int (u+4)(2u+1) du =...

Asked by enotes on via web

• Math
intv(v^2+2)^2dv =intv((v^2)^2+2v^2*2+2^2)dv =intv(v^4+4v^2+4)dv =int(v^5+4v^3+4v)dv apply the power rule, =v^6/6+4v^4/4+4v^2/2+C , C is constant =v^6/6+v^4+2v^2+C

Asked by enotes on via web

• Math
int(x^3-2sqrt(x))/xdx Simplify by dividing each term in the numerator by x.  <br>  =(x^3/3)-(2x^(1/2))/(1/2)+C =(x^3/3)-4x^(1/2)+C   

Asked by enotes on via web

• Math
int(x^2+1+1/(x^2+1))dx apply the sum rule, =intx^2dx+int1dx+int1/(x^2+1)dx To evaluate the above integrals, we know that, intx^ndx=x^(n+1)/(n+1) and int1/(x^2+1)dx=arctan(x) using above,...

Asked by enotes on via web

• Math
We have to find the integral : \int (sin(x)+sinh(x) )dx=-cos(x)+cosh(x)+C where C is a constant.

Asked by enotes on via web

• Math
int(csc^2(t)-2e^t)dt Apply the sum rule, =intcsc^2(t)dt-int(2e^tdt We now the following common integrals, intcsc^2(x)=-cot(x) and inte^xdx=e^x evaluate using the above, =-cot(t)-2e^t+C...

Asked by enotes on via web

• Math
You need to evaluate the indefinite integral, such that: int f(theta)d theta = F(theta) + c int (theta - csc theta* cot theta)d theta = int theta d theta - int (csc theta* cot theta)d theta...

Asked by enotes on via web

• Math
y=sec^2(x) Refer the graph in the attached image. From the graph, Area of the region beneath the curve ~~ 4/10(Area of the Rectangle) Area of the region=~~(4/10)(pi/3*4) Area of the...

Asked by enotes on via web

We have to evaluate the integral and interpret as difference of areas. So, \int_{-1}^{2}x^3dx=[x^4/4]_{-1}^{2} =[(2^4)/4]-1/4 =16/4-1/4 =15/4=3.75` So...